Myofibroma of the upper lip free edge mimicking a hyperkeratotic plaque - Azañero, Wilson Alejandro Delgado; Dulanto, Victor Manuel Arrascue; Valdez, Luciano Hermios Matos; Sanchez, Katman Bear Toledo (Journal of Oral Diagnosis, 2025)
Myofibroma is a benign, non-encapsulated neoplasm that predominantly affects the skin and subcutaneous tissue of the head and neck. It has been documented in various regions of the oral mucosa and jawbones. However, cases involving the free edge of the lips have not been previously reported. We present a case of myofibroma manifesting as a yellowish-white plaque on the free edge of the upper lip, initially misdiagnosed as a hyperkeratotic plaque. Consequently, myofibromas may also present as flat lesions, rather than as swellings or tumors, potentially mimicking an epithelial disorder. The lesion was completely excised, and after a four-month follow-up, no recurrence was observed.